Assessing the Role of Vaccination in the Control of Hand, Foot, and Mouth Disease Transmission - Zuhur Alqahtani; Mahmoud H. DarAssi; Yousef AbuHour; Areej Almuneef (Mathematics)
The impact of vaccination on the dynamics of hand, foot, and mouth disease (HFMD) transmission is explored in this paper, considering a fractional-order derivative system of equations. This model provides vaccination strategies and characterizes local and global stability using Lyapunov functions. This work computes the basic reproduction number (<semantics>R0</semantics>) to represent the endemic and epidemic scenarios. Additionally, sensitivity analysis was performed to identify the most critical parameters responsible for the disease dissemination. Our results indicate that vaccination plays a crucial role in controlling HFMD, significantly reducing its prevalence. These findings align with existing research, supporting the importance of effective vaccination strategies and public health interventions against HFMD. The fractional-order model captures the memory effect in infectious disease dynamics, providing further insight into modeling HFMD transmission compared to a traditional integer-order model. The results would contribute to effective vaccination strategies and public health interventions against HFMD.